2020
DOI: 10.1002/ehf2.12896
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma phenylalanine predicts mortality in critical patients with heart failure

Abstract: Aims Previous studies found a relationship between elevated phenylalanine levels and poor cardiovascular outcomes. Potential strategies are available to manipulate phenylalanine metabolism. This study investigated whether increased phenylalanine predicted mortality in critical patients with either acute heart failure (HF) or acute on chronic HF, and its correlation with inflammation and immune cytokines. Methods and results This study recruited 152 subjects, including 115 patients with HF admitted for critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…Moreover, Chen et al have recently reported that phenylalanine predicted mortality in critically ill patients with acute heart failure (HF) or acute on chronic HF. [32] In multivariate analysis, phenylalanine levels ≥ 112 μM predicted death over one year, regardless of age, APACHE II and SOFA scores, atrial fibrillation, C-reactive protein, cholesterol, prealbumin, transferrin, and IL-8 and IL-10. Thus, a growing body of evidence points to phenylalanine as a marker of disease severity, especially related to respiratory distress.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Chen et al have recently reported that phenylalanine predicted mortality in critically ill patients with acute heart failure (HF) or acute on chronic HF. [32] In multivariate analysis, phenylalanine levels ≥ 112 μM predicted death over one year, regardless of age, APACHE II and SOFA scores, atrial fibrillation, C-reactive protein, cholesterol, prealbumin, transferrin, and IL-8 and IL-10. Thus, a growing body of evidence points to phenylalanine as a marker of disease severity, especially related to respiratory distress.…”
Section: Discussionmentioning
confidence: 96%
“…There are considerable evidence convincing the alterations of BCAA during HF, but these studies fail to explain the underlying mechanisms of how BCAA contributes to the progression of HF. Large-scale trails, to date, have been carried out to demonstrate the relationship between circulating phenylalanine concentrations and HF (34,35,37,(56)(57)(58)(59). Most of them suggest that increased phenylalanine could provide both diagnostic and prognostic value for HF.…”
Section: Dysregulated Amino Acid Metabolism In Heart Failurementioning
confidence: 99%
“…Large-scale trails, to date, have been carried out to demonstrate the relationship between circulating phenylalanine concentrations and HF ( 34 , 35 , 37 , 56 59 ). Most of them suggest that increased phenylalanine could provide both diagnostic and prognostic value for HF.…”
Section: Dysregulated Amino Acid Metabolism In Heart Failurementioning
confidence: 99%
See 2 more Smart Citations